ANALYSIS OF RESPONSIBILITY CHARACTER OF THE FIFTH GRADE STUDENTS AT SD NEGERI 136 PEKANBARU - Nur’aini; Lazim N (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This quantitative descriptive research aims at describing the character of responsibility of the fifth grade students at SDN 136 Pekanbaru. The research was conducted because the students were lack of awareness in responsibility both at school and at home. The population of this research was all of the fifth grade students at SDN 136 Pekanbaru with 136 students and the number of sample was 48 students which were chosen by using questionnaires and interviews. The results showed that the fifth grade students of SDN 136 Pekanbaru were responsible both at school and at home. It can bee seen from the results of the analysis of students doing homework by 74.48%, repeating lessons at home by 58.68%, helping parents at home with 66.87%, doing class picket assignments by 70.31%, doing group assignments together with groups by 68.75%, doing individual tasks by 70.31%, keeping the school clean by 69.44%, apologizing to friends when guilty by 61.20%. It can be concluded that the fifth grade students of SDN 136 Pekanbaru were responsible both at home and at school. Thus, the school and the teacher should be able to build the character of responsibility at school.